The effect of using Eisencraft's inquiry model on learning some rope skills in rhythmic gymnastics for female students - Mohamed, L.Dr.Solaf Mouloud; Yawar, ِAsst.Prof.Dr. Firas Ajil (Sulaimani Journal for Humanities, 2025)
The research aimed to identify the effect of Eisencraft's model on the learning of some basic rhythmic gymnastics skills for female students. The research problem stemmed from the researchers' observation of a weakness in the use of modern models in teaching basic rhythmic gymnastics skills to female students, and a lack of consideration for scientific, cognitive, and technological advancements in all sports in general, and in the field of gymnastics in particular. The researchers hypothesized the existence of statistically significant differences in the post-test results between the control and experimental groups in the variables under study. The research population was selected purposively from female students of the College of Physical Education, totaling (45) students. They were randomly selected and divided by lottery into two groups: an experimental group of (20) students and a control group of (20) students. The number of students in the pilot sample was (5) students. The researchers prepared instructional units according to Eisencraft's model and applied them to the members of the experimental group, while the members of the control group underwent instructional units prepared by a specialized coach. The training kit was used. The ready-made SPSS statistical tool was used to draw conclusions, as the research results showed an improvement in the basic skills tests for rhythmic gymnastics for the experimental group. Based on the research results, the researchers recommend adopting Eisencraft’s model in teaching the basic skills of rhythmic gymnastics to female students.
Keywords: Eisencraft Model; Rope Skills; Rhythmic Gymnastics